2020
DOI: 10.48550/arxiv.2010.11416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rank-structured QR for Chebyshev rootfinding

Abstract: We consider the computation of roots of polynomials expressed in the Chebyshev basis. We extend the QR iteration presented in [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The relationship between componentwise perturbations to the colleague matrix and the backward error in the coefficients was described completely in 2019 by Noferini, Robol, and Vandebril in [27]. Recently (see [32] and [14]), it was observed that certain O(n 2 ) structured QR algorithms for colleague matrices are surprisingly stable, attaining the bound (2) in many cases, an observation that mirrors the discovery in [3] for the case of companion matrices. However, unlike in [3], all previously proposed O(n 2 ) structured QR algorithms for colleague matrices have polynomials for which the worst-case bound (4) is attained.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…The relationship between componentwise perturbations to the colleague matrix and the backward error in the coefficients was described completely in 2019 by Noferini, Robol, and Vandebril in [27]. Recently (see [32] and [14]), it was observed that certain O(n 2 ) structured QR algorithms for colleague matrices are surprisingly stable, attaining the bound (2) in many cases, an observation that mirrors the discovery in [3] for the case of companion matrices. However, unlike in [3], all previously proposed O(n 2 ) structured QR algorithms for colleague matrices have polynomials for which the worst-case bound (4) is attained.…”
Section: Introductionmentioning
confidence: 91%
“…Lemma 2.5. Suppose that Q ∈ SU( 2) is a complex rotation matrix, and let Q be a floating point approximation to Q satisfying (14). Suppose further that…”
Section: Multiplication By Complex Plane Rotationsmentioning
confidence: 99%
See 3 more Smart Citations